Desarrollo de negocios para el impulso de emprendimientos turísticos en la ciudad de Guaranda. año 2019” - Chiriboga Secaira, Daniel Alejandro (2020)
The promotion of tourism in the city of Guaranda through entrepreneurship is possible after knowing the current situation of the tourism system, increasing strategies for the development of tourism ventures by establishing clear guidelines to establish a business plan model that will help the economic advance of the population of the city of Guaranda. For the fulfillment of the present investigation, we worked in phases, the first one that allowed us to carry out a tourist diagnosis, the second one was developed in a participatory way through working groups with the actors of the tourism sector and finally the guidelines with which we can have a business plan model in tourism ventures. It can be defined that in the city of Guaranda it is necessary to establish a business model for tourism ventures that helps the economic development of the population of the city of Guaranda, it is important for people who wish to undertake a tourism project and who do not have the sufficient experience of how to do it, this should not be a reason for not starting your business, because they can compensate for this lack of experience with a good preparation, they can also associate or advise with people who have it and who have the professional technical knowledge, In this way the venture will have the desired success.